The apocalypse of St John the Greek text with introduction, notes and indices - Swete, Henry Barclay, 1835-1917 (London, UK MacMillan, 1909)
Includes index, maps, etc.
1917 reprint of 1909 edition. First edition published 1906, which see also (stacks). Second edition published 1907.
Keywords: Bible. N.T. Revelation -- commentaries